1999
DOI: 10.1089/10430349950016537
|View full text |Cite
|
Sign up to set email alerts
|

Combined Ultrafiltration-Transduction in a Hollow-Fiber Bioreactor Facilitates Retrovirus-Mediated Gene Transfer into Peripheral Blood Lymphocytes from Patients with Mucopolysaccharidosis Type II

Abstract: The process of growing and transducing large quantities of human primary peripheral blood lymphocytes (PBLs) with high gene transfer efficiency continues to be one of the major challenges for clinical and experimental gene therapy. Toward developing a clinical trial of lymphocyte gene therapy for mucopolysaccharidosis type II (i.e., Hunter syndrome), we investigated a novel method that exploited the innate capability of a hollow-fiber bioreactor system to filter large quantities of vector supernatant and facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Some of these difficulties could be circumvented by the use of improved viral vectors, virus purification conditions [72, 73, 74], transduction procedures, and viral packaging cell lines [75, 76, 77, 78, 79, 80]. Moreover, the expansion, transduction, and selection of target cells, like BM stem cells, in vitro have been facilitated by the use of specific cell culture conditions and selectable markers [a].…”
Section: Gene Transfer and Gene Therapy For Lysosomal Storage Diseasementioning
confidence: 99%
“…Some of these difficulties could be circumvented by the use of improved viral vectors, virus purification conditions [72, 73, 74], transduction procedures, and viral packaging cell lines [75, 76, 77, 78, 79, 80]. Moreover, the expansion, transduction, and selection of target cells, like BM stem cells, in vitro have been facilitated by the use of specific cell culture conditions and selectable markers [a].…”
Section: Gene Transfer and Gene Therapy For Lysosomal Storage Diseasementioning
confidence: 99%
“…CHO (Chinese‐hamster ovary) cells [28–30], murine erythroleukaemia cells [31], mouse mammary tumour cells S115 [32], human prostate carcinoma cells LNCaP (human prostate carcinoma cells) [33], BHK‐21 (baby‐hamster kidney 21) cells producing a chimaeric human monoclonal antibody [34] and patented human hepatoblastoma C3A cells [35]. Other cell lines grown in an HFB include human T‐lymphocytes for cytokine production [36], human lymphocytes for gene therapy [37] and gene transfer [38] and human hepatocellular liver carcinoma cell line Hep G2 [39]. HFBs were used for retroviral vector production [40,41], for co‐culturing rat endothelial and rat glial cells to simulate the blood/brain barrier [42] and to create artificial organs like liver [43–45], kidney [43] and pancreas [46].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, such systems have been used for production of industrial and clinical‐grade reagents such as monoclonal antibodies 24, cell lines 25, 26, and other biologics destined for pharmacological applications 27, 28. In our previous work 29, we have demonstrated that an HBS could be used to culture and transduce human primary peripheral blood lymphocytes (PBL) in clinically useful quantities (up to 10 10 primary PBL). Moreover, gene transfer efficiency was improved (up to 57%) in these large amounts of PBL without the use of centrifugation, fibronectin, or other special manipulations.…”
Section: Introductionmentioning
confidence: 99%